Symptom Burden, Health Status, and Productivity in Patients with Uncontrolled and Controlled Severe Asthma in NOVELTY - Ding B; Chen S; Srivastava D; Quinton A; Cook W; Papi A; Reddel HK (Journal of Asthma and Allergy, 2023)
Bo Ding,1 Stephanie Chen,2 Divyansh Srivastava,3 Anna Quinton,4 William Cook,2 Alberto Papi,5 Helen K Reddel,6 on behalf of the NOVELTY Scientific Community and the NOVELTY study investigators1BioPharmaceuticals Medical, AstraZeneca, Gothenburg, Sweden; 2BioPharmaceuticals Medical, AstraZeneca, Gaithersburg, MD, USA; 3ZS Associates, Pune, India; 4BioPharmaceuticals Business Unit, AstraZeneca, Cambridge, UK; 5Department of Translational Medicine, Università di Ferrara, Ferrara, Italy; 6The Woolcock Institute of Medical Research and the University of Sydney, Sydney, NSW, AustraliaCorrespondence: Bo Ding, AstraZeneca, Pepparedsleden 1, Mölndal, SE 431 83, Gothenburg, Sweden, Tel +46 31 776 2406, Email bo.ding@astrazeneca.comBackground: Few studies have quantified symptom burden, health status, and productivity in patients with uncontrolled and controlled severe asthma. Up-to-date, real-world, global evidence is needed.Objective: To quantify symptom burden, health status, and productivity in patients with uncontrolled and controlled severe asthma using baseline data from the NOVEL observational longiTudinal studY (NOVELTY; NCT02760329).Methods: NOVELTY included patients aged ≥ 18 years (or ≥ 12 years in some countries) from primary care and specialist centres in 19 countries, with a physician-assigned diagnosis of asthma, asthma+chronic obstructive pulmonary disease (COPD), or COPD. Disease severity was physician-assessed. Uncontrolled severe asthma was defined by an Asthma Control Test (ACT) score < 20 and/or severe physician-reported exacerbations in the previous year; controlled severe asthma required an ACT score ≥ 20 and no severe exacerbations. Assessment of symptom burden included Respiratory Symptoms Questionnaire (RSQ) and ACT score. Assessment of health status included St George’s Respiratory Questionnaire (SGRQ), EuroQoL 5 Dimensions 5 Levels Health Questionnaire (EQ-5D-5L) index value, and EQ-5D-5L Visual Analog Score (EQ-VAS). Assessment of productivity loss included absenteeism, presenteeism, overall work impairment, and activity impairment.Results: Of 1652 patients with severe asthma, asthma was uncontrolled in 1078 (65.3%; mean age 52.6 years, 65.8% female) and controlled in 315 (19.1%; mean age 55.2 years, 56.5% female). With uncontrolled versus controlled severe asthma, symptom burden was higher (mean RSQ score 7.7 vs 2.5), health status more impaired (mean SGRQ total score 47.5 vs 22.4; mean EQ-5D-5L index value 0.68 vs 0.90; mean EQ-VAS score 64.1 vs 78.1), and productivity lower (presenteeism 29.3% vs 10.5%).Conclusion: Our findings highlight the symptom burden of uncontrolled severe asthma compared with controlled severe asthma and its impact on patient health status and productivity, and support the need for interventions to improve control of severe asthma.Graphical Abstract: Keywords: asthma control, health status, productivity, symptom burden, symptom control, uncontrolled severe asthma